Deteksi Mikroplastik pada Udang Vannamei (Littopenaeus vannamei) dari Pasar Beringharjo Kota Yogyakarta - Nurul Suwartiningsih; Alya Luthfiyya Ariefiani Putri; Dian Eka Wijayanti; Adhita Sri Prabakusuma (Universitas Sebelas Maret, 2023)
Microplastics in the bodies of aquatic biota can have a negative impact either on aquatic biota or humans who consume them. One of the largest markets in Yogyakarta that sells aquatic commodities is Beringharjo Market. This research was done to analyze the abundance and characteristics of microplastics contained in the digestive tract and meat of vannamei shrimp (Litopenaeus vannamei) sold at Beringharjo Market. Microplastics were isolated from digestive tract and meat using 10% KOH at room temperature for three days. The microplastics are then filtered and observed under a microscope. The average abundance of microplastics in the digestive tract and meat was analyzed using Mann-Whitney test. The results showed that the abundance of microplastics in the digestive tract (933.00 ± 380.17 microplastics/gram) was higher than in meat (759.25 ± 254.21 microplastics/gram), but was not significantly different (p>0, 05). The average of fragments and fibers microplastics between the digestive tract and meat was significantly different (p<0.05), while the average of films and pellets microplastics was not significantly different (p>0.05). The color of microplastics was not significantly different (p>0.05). The most dominant size of microplastics is in the range of 0-100 μm, each at 40%. FT-IR results showed that the vannamei shrimp samples contained nylon type microplastics. Microplastics in the digestive tract and meat of vannamei shrimp sold at Beringharjo Market have the same abundance and characteristics.